Analysis of the trade-off between voltage gain and frequency response of OTA designed using experimental data of omega-gate nanowire SOI MOSFETs - De Araujo, Gustavo V.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this paper the Omega-gate nanowire (NW) transistor applied for designing Operational Transconductance Amplifier (OTA) is studied, focusing mainly on the trade-off between voltage gain (Av) and gain-bandwidth product (GBW). One option to determine a good compromise between gain and frequency response is to get a bias condition where the product Av ∗ GBW reach the maximum values. For NW nMOSFET and pMOSFET the maximum product occurs for gm/ID = 11 V-1 and 10 V-1 respectively. OTA simulations were realized based on experimental data using Verilog A language with look up table method. The circuit was created using Cadence's Spectre showing great results for the omega-gate nanowire as a voltage gain of 1122 V/V and a GBW of 602 MHz for a gm/ID of 8 V-1. Our work shows that the best results for OTA circuit was obtained when the transistor efficiency is gm/ID = 8 V-1, different of the values got from individual transistors.
Keywords: Analog Circuit Design; Nanowire; Omega-gate; Operational Transconductance Amplifier (OTA)